If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) = (x + 4) Reorder the terms: 3(-2 + x) = (x + 4) (-2 * 3 + x * 3) = (x + 4) (-6 + 3x) = (x + 4) Reorder the terms: -6 + 3x = (4 + x) Remove parenthesis around (4 + x) -6 + 3x = 4 + x Solving -6 + 3x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 3x + -1x = 4 + x + -1x Combine like terms: 3x + -1x = 2x -6 + 2x = 4 + x + -1x Combine like terms: x + -1x = 0 -6 + 2x = 4 + 0 -6 + 2x = 4 Add '6' to each side of the equation. -6 + 6 + 2x = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 4 + 6 2x = 4 + 6 Combine like terms: 4 + 6 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 2x+16=5x+80 | | 4/9/-6 | | (5x-6)(x-6)=36 | | 12x/7y/x | | (x^(-2/5)y^(1/3))^15 | | 4x=-3x+2 | | (7i)(-8i)= | | M^2+8m-55=0 | | 8x^4-12x^3-6x^2/4x^2 | | H(0)=-20x^2+44x-21 | | 4Y^4=28Y | | 72=3n+9+n-2 | | -16+x+x=-15 | | 19(7+w+(-2))= | | 3-2x=c | | e-3.4x+1.5=2.5 | | 16t(8r+3v)= | | (3x+1.3)+(4x-3.8)=180 | | 13x+y=40 | | 7p+11=-5 | | x=5-y-9 | | 3x+5y=-26 | | -6-6x+7x=16 | | 5x-8x-11=-3x+4-11 | | -3(x+5)=2(10+x) | | 8n^2-16n-6=0 | | Y-2=8/9(x-9) | | 123+2h=927 | | 2(x+2)+7=6x-4(-2+x) | | 3x+10y=-10 | | 7x/26=12/59 | | 16cos^2x-1=0 |